MEKANISME PEMBERHENTIAN PRESIDEN DAN/ATAU WAKIL PRESIDEN SETELAH PERUBAHAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - PUTRA, AGUS TRIOKA MAHENDRA (Fakultas Hukum Universitas Dwijendra, 2015)
ABSTRACTÂ This research is addressed to two main subject. The first one, how was the president and/or vice president impeachment in the history of public constitution of Republic of Indonesia as well as its comparison with other countries? And the second one, what was the impeachment mechanism of president and/ or vice president after the amendement of Republic of Indonesia Constitution of 1945? Â The subjects are studied by using a method of normative legal research with statute approach and legal analytical and conceptual approach as well as comparative approach. The legal collected materials were analyzed qualitatively using interpretation method and legal argumentation. The research shows that the impeachmen mechanism of president and/ or vice president after the 1945 Constitutions amendement was not clearly arranged on the procedure and the legal reason to implement the impeachment. The 1945 Constitution of Republic of Indonesia does not mention the matter explicitly and in detail. The Constitution only regulates the handover of power from president to vice president in case of the president passes away, resigns or unable to perform his obligation within the period of his duty as written in the Article 8 of 1945 Constitution of Republic of Indonesia. That the legal norm says that the phrase â?? the House of Representative opinionâ? formulated in Article 7B of 1945 Constitution is vague and inconsistent and may raise interpretation. Through this thesis, it is suggested that the House Representative complete stipulation of the rule of the law which concerns the mechanism of president and/ or vice president impeachment. Related to impeachment mechanism at the Constitution Court: the court should arrange and draw up Regulation of Constitution Court which describes the implementation of judicature in detail based on the House Representative opinion which accuses president and/ or vice president of being breaking obstructing the law.Â Key Words: Presidents impeachment mechanism, substitution of power, Act, obstruction of the law.Â Â Â Â Â Â Â Â Â Â Â Â Â Â